Hukum Membuka Tempat Makan Pada Siang Ramadan (Analisis Hukum Islam Dengan Pendekatan Usuliyah) - Muttaqin, Imamul (Al-Fikru: Jurnal Ilmiah, 2021)
This research aims to analyze the law of opening a place to eat during the month of Ramadan using usuliyah analysis. The research method used is qualitative with the Ushuliyah approach. The data source used was the jurisprudence books from several schools related to the research topic. The results showed that: (1) it is permissible to sell food to people who have not been obliged to fast, are unable to fast or are given relief not to fast, such as small children, women who are menstruating and people who are sick. Likewise, it is also permissible if the food will be consumed when not fasting, such as for breaking the fast or for eating sahur. (2) It is forbidden to sell food to a person who is obliged to observe fasting if he knows or thinks (dzon) that the food will be consumed during the day because this is considered to help immorality. If he does not know whether the food will be consumed during the day or not, then the law is makruh and it is better not to sell food to that person. That is why some scholars have issued a fatwa to close places where food and drinks are sold during the fasting month. (3) Trading or opening a place to eat for special reasons only for unbelievers, cannot be used as evidence.